Pengaruh Penggunaan Multimedia Interaktif terhadap Hasil Belajar Interaksi Manusia dan Komputer di Universitas Hamzanwadi - Ahmad Fathoni (Universitas Hamzanwadi, 2017)
The aims of this research were to describe and analyze the influence of interactive multimedia-based learning media toward learning outcome of computer human interaction (HCI) course. This research is a survey research with quantitative approach to a research survey. The population and sample in this research is the entire semester III students among them is a class IIIA and IIIB totaling 50 students. The instrument of data collecting in this research is a questioner. The method used for data analysis in this research is descriptive statistics. The results of this research show that the variables X and Y approach the high category with the percentage of successively 71.72%, and 75%. The application of interactive multimedia-based learning media in various learning is one of the solutions to create interesting, innovative, challenging and able to think independently.